The novel house dust mite allergen Der p 39 exacerbates atopic dermatitis-like inflammation in mice by inducing skin barrier dysfunction - Shan Liu, BSc; Ze-Lang Cai, MS; Jingcheng Liu; Si-Yi Que, BSc; Wan-Zhen Hu, MS; Liang Chen, MS; Jia-Jie Chen, PhD; Kunmei Ji, PhD (World Allergy Organization Journal)
Background: House dust mite (HDM) allergens can induce or exacerbate allergic inflammation, including atopic dermatitis (AD). Substances that damage the epithelial barrier can trigger or worsen AD. The mechanism by which the novel HDM allergen Der p 39 induces allergic inflammation remains unclear. Our aim was to investigate the effects of Der p 39 on AD-like inflammation and associated mechanisms. Methods: Dinitrochlorobenzene (DNCB) and Der p 39 were utilized to establish AD model mice. Inflammation severity was evaluated with physiological and morphological assays. The effects of Der p 39 on inflammatory cytokine release and skin barrier protein expression were examined in HaCaT cells (human epidermal keratinocytes). Mitogen-activated protein kinase (MAPK) activation was examined by western blots. MAPK inhibitors were employed to assess MAPK involvement in filaggrin expression. Results: Der p 39 worsened allergic inflammation (tissue thickness) in murine ears pretreated with 1% DNCB. Compared to controls, Der p 39-sensitized tissues showed epidermal and dermal thickening with elevated numbers of mast cells and eosinophils in inflammatory lesions. Der p 39 increased transcription and production of pro-inflammatory interleukins (ILs), down-regulated expression of the skin barrier proteins filaggrin and loricrin, and upregulated phosphorylation of ERK, JNK and p38 in HaCaT cells. Inhibition of MAPK signaling rescued filaggrin expression in Der p 39-treated cells. Conclusions: The HDM allergen Der p 39 enhances allergic inflammation and promotes MAPK pathway-mediated epidermal barrier dysfunction, suggesting that Der p 39 may possess pathogenic and clinically relevant immunomodulatory potential.